Measuring the rate of technological change in Chinese rubber smallholdings - a micro-economic approach - Chew, T. A. (Rubber Research Institute of Malaysia, 1984)
Technological progress is commonly measured via aggregate production functions. In this paper, technological progress is estimated from a micro-economic viewpoint. A Cobb-Douglas production function was fitted to two sets of + cross-sectional data collected at different points in time. From the estimates obtained, we derived that the rate of technological progress in rubber smallholdings is the capital-augmenting type at about 1.2% per year.